Deep Learning: a Theoretical Review - Fauziati, Endang (SUAR BETANG, 2025)
The term Deep Learning has become the current issue in educational field all around the globe. Deep learning is true learning, in the sense, that it is enduring, as opposed to shallow or surface learning that tends to be momentary. This term was proposed by Fullan et al. to refer to the process of acquiring the global competencies known as the 6Cs: character, citizenship, collaboration, communication, creativity, and critical thinking. These competencies are suitable to prepare students to be confident in encountering globalization challenges. Deep learning is designed based on a new pedagogical model, a learning partnership between and among students and teachers to master of content knowledge, create and use new knowledge in the real world. The focus of teaching is to develop students’ ability to manage their own learning and to do things with their learning. In Indonesian context, Deep Learning is implemented based on a framework consisting of four main components: learning framework, learning experience, learning principle, and graduate profile dimension framework. The learning experience framework includes three aspects: understanding, applying and reflecting. In practice, Deep learning is based on three main learning approaches mindful learning, meaningful learning, and joyful learning.